The application of genetic mapping in the identification of breast cancer polymorphisms and the targeting of targeted therapy (Research, Society and Development, 2022)
Breast cancer is characterized by a genetic mutation, where the deregulation of the cell cycle of breast cells occurs. Genetic mapping serves as an apparatus and understanding between the genomic organization and the relationship between genes and the phenotype of breast cancer. Objective: To carry out an updated review of the literature regarding the use of genetic mapping in oncology practice, in addition to highlighting the importance of understanding genetic aspects for targeting personalized therapy and clinical follow-up in breast cancer. Methodology: This is an exploratory study of integrative literature review, with searches performed on the following platforms: PubMed, Google Scholar and Scientific Electronic Library Online (Scielo); in the period from 2012 to 2021 and the inclusion criteria were articles that address issues related to discussions about the application of genetic mapping in the identification of breast cancer polymorphisms and targeting therapy, all published in the last ten years. Among the exclusion criteria were those who did not fit the inclusion criteria. Result: 26 publications were selected, which met the exclusion criteria, namely: 5 publications in the PUBMED database, 6 in the Scielo database and 15 in the academic Google. Conclusion: Genetic research plays a fundamental role in the recognition of BRCA1 and BRCA2 gene mutations. Thus, allowing the personalized therapeutic application in breast cancer, although still not very accessible, it is of enormous importance for medicine, contributing to increased survival and well-being of each patient.